Peningkatan Kecerdasan Logis Matematis Melalui Model Pembelajaran Generatif Pada Siswa Kelas 5 Sekolah Dasar Negeri Rambutan 03 Pagi - Putri Pertiwi, Amelia; Yurniwati; Soleh, Dudung Amir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of logical mathematical intelligence in elementary school students frequently does not reach optimal levels, particularly when mathematics instruction relies on conventional teacher-centered approaches. Such methods often provide limited opportunities for students to explore concepts actively, recognize relationships, and apply reasoning skills in solving mathematical problems related to the area and perimeter of plane figures. This classroom action research was designed to enhance logical mathematical intelligence by implementing the Generative Learning Model, which emphasizes stages of exploration, focusing, challenge, and application. The study involved 29 5B students of SD Negeri Rambutan 03 Pagi and was conducted in three cycles comprising planning, action, observation, and reflection. Data were collected through observation sheets to record learning activities and essay tests to measure logical mathematical intelligence across indicators including calculation, problem-solving, pattern recognition, inductive and deductive reasoning, and cause-effect analysis. The results showed consistent improvement both in students’ performance and engagement. The average test scores increased from 58 in the pre-cycle and 68 in Cycle I, 81 in Cycle II, and 85 in Cycle III. Observations revealed that students became more active in discussing solutions, more confident in applying formulas, and more accurate in performing calculations. These findings indicate that the Generative Learning Model is effective in developing logical mathematical intelligence and offers a promising instructional strategy to support mathematics learning in elementary education.